Adherence to physical activity recommendations and associations with self-efficacy among Norwegian adolescents: trends from 2017 to 2021 - Grasaas, Erik; Sandbakk, Øyvind (Frontiers in Public Health, 2024)
The crucial role of physical activity (PA) in promoting well-being and overall health of adolescents is widely acknowledged. Previous global studies have consistently revealed low adherence to PA recommendations among adolescents, emphasizing potential links between PA engagement and self-efficacy in school-based populations.However, there is a need for further exploration of this relationship, in particularly gender differences and taking into account the potential influences of the COVID-19 pandemic. The objective of this study is to provide a comprehensive description of adherence to PA recommendations and its associations with self-efficacy in Norwegian school-based adolescents over the period from 2017 to 2021.Methods: Cross-sectional data on physical activity (PA) levels and self-efficacy among 13-19-year-old Norwegian adolescents were collected from the Norwegian Ungdata Survey during the period 2017 to 2021. The survey, conducted in Norwegian lower-and upper-secondary schools, was administered electronically during school hours. All data collected is anonymous and has received approval from the Norwegian Agency for Shared Services in Education and Research (SIKT). Statistical analyses were performed using SPSS software.Results: Girls consistently exhibited lower adherence to PA recommendations (17.6%-19.8%) compared to boys (27.7%-31.1%) each year from 2017 to 2021 (all p<0.01). Similarly, girls reported lower self-efficacy (14.1 to 14.8 out of 20) than boys (15.5 to 15.9) during the same period (all p<0.01). Regression analyses highlighted robust positive associations between PA and self-efficacy in those adhering to PA recommendations (i.e., physically active at least 5 times a week) and strong inverse associations for those reporting inactivity (never active) in both girls and boys from 2017 to 2021.Adolescents in Norway report PA adherence ranging from 15% to 30%, with girls consistently exhibiting lower adherence to PA recommendations and reporting lower self-efficacy than boys. Notably, there are substantial associations between self-efficacy and both adherence to PA recommendations and inactivity over time. These findings underscore the significance of promoting adherence to PA recommendations during adolescence, especially among girls.Policymakers in Norway should focus on initiatives to increase PA levels among adolescents in both lower and upper secondary schools.